The effects of international migration on native workers' unionisation in Austria - Jose-Ignacio Anton; René Böheim; Rudolf Winter-Ebmer (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
We analyze the effects of increased immigration of foreign workers on the unionisation rates of native workers in Austrian firms over the period 2002-2012. Our results suggest that lower union density of natives' in firms with more foreign workers is driven not by natives leaving unions, but by the different composition of turnover depending on the share of foreigners in the firm.
Keywords: J51; J61; J63; 330; migration; unions; turnover; hiring